Newborn with Harlequin Ichthyosis and the Nursing Care - Serap Torun; Handan Demiroğlu (Galenos Yayinevi, 2018)
Harlequin ichthyosis is the severest form of non-bullous ichthyosis, which is quite uncommon in newborns, and is usually characterized by fatal extreme keratinization of the skin. Because of the facial appearance of newborn, which resembles clown, the disease is called as harlequin -one of the comic characters of Italian street theatre. The present case report concerning a newborn with harlequin ichthyosis, which is an uncommon condition requiring intensive care, aimed to guide the care process by discussing the experiences over the nursing care period. Within the scope of nursing process, the data were collected, the diagnoses were identified, interventions were planned and implemented, and the outcomes of these implementations were evaluated. The nursing diagnoses were made based on the diagnosis list established by the North American Nursing Diagnosis Association. Nursing process was performed within the scope of the activities of daily living. Life expectancy of the patient, who was expected to die within a few days after birth, was extended by efficient and preventive nursing care, but these implementations have not been sufficient to prolong survival. Specific to this case, we can say that death could be postponed by nursing care. Palliative and preventive care is recommended when harlequin ichthyosis is encountered.